Simply rich : - DeVos, Richard M (Howard Books, 2014)
A prominent businessman, self-made billionaire, philanthropist, worldwide speaker, bestselling author, family man, and devout Christian-few people embody the heart of entrepreneurial spirit as plainly as Rich DeVos. He not only helped create one of the world's biggest companies-Amway-but he did it from the ground up. Now, following on the success of DeVos's bestselling books about the world of business, he reveals his personal story for the first time ever. Simply Rich is a candid telling of his journey from rags to riches, from a small start-up business to giant success, and from doubts to dreams come true.